Computers in our world, today and tomorrow - Hintz, Sandy; Hintz, Martin (New York : Franklin Watts, 1983)
Describes the roles of computers, now and in the future, in the spheres of medicine, business and government, law enforcement, science and technology, entertainment, education, and the home. Includes a glossary of terms.
Includes index.
Booklist
School Library Journal
8.5
5-8.
5-8
Keywords: Computers; Computers; Computers -- Juvenile literature; Data processing; Data processing; Electronic data processing -- Juvenile literature